Review On Bio-Fertilizers, Substitution of Synthetic Fertilizers in Cereals for Leveraging Agriculture (International Journal of Food and Nutritional Sciences, 2022)
Crop plants need essential nutrients such as nitrogen and phosphorus to grow and develop. Extreme environmental risks have been reported as a result of the overuse of synthetic fertilizers. As a result, bio-fertilizers have a huge potential to enhance plant nutrition while also being environmentally benign by replacing synthetic fertilizers. Bio-fertilizers have a fantastic propensity to reduce the need for synthetic fertilizers while maintaining crop production. Plant growth promoting rhizobacteria (PGPR) such as Azotobacter and Azospirillum, as well as phosphorus solubilizing bacteria (PSB) such as Pseudomonas sp. and Bacillus sp., are found in bio-fertilizers and are capable of fixing atmospheric nitrogen and solubilizing soil phosphorus, respectively. As a result, they meet cereals' nitrogen and phosphorus requirements while simultaneously improving soil fertility. As a result, employing nitrogen-fixing and phosphorus-solubilizing bacteria as bio-fertilizers offers enormous potential for utilising atmospheric nitrogen and fixed phosphorus in the soil in crop production while causing no damage to the aerial and soil environment. Bio-fertilizers are more cost-effective than synthetic fertilizers owing to lower market costs, and they aid in strengthening soil structure and environmental restoration for agricultural leverage.